(untitled) (Revista Cocar, 2021)
Este artigo tem como tema de investigação a relação entre a história de um intelectual orgânico do estado do Pará, Ilha de Marajó, microrregião de Portel, município de Gurupá, e a luta em defesa do acesso à educação. Tem-se como objetivo descrever a história de vida desse intelectual em meio a acontecimentos mais gerais que resultaram, dentre outros feitos, na criação da Casa Familiar Rural de Gurupá e sua proposta de educação para os (as) jovens da região. Teoricamente, o estudo pautou-se na história vista de baixo, de Thompson, e na concepção de intelectual orgânico de Gramsci. Metodologicamente, trabalhou-se com a História Oral. Utilizou-se como fontes: documentos recolhidos no município de Gurupá, dados de um memorial escrito por Manoel do Carmo e dados de entrevistas semiestruturadas. Após a análise, foi possível constatar que a vida de Manoel do Carmo está indelevelmente articulada às lutas sociais do Município de Gurupá, vinculadas aos trabalhadores do campo e educação. Palavras-chave: Intelectual Orgânico; Movimentos Sociais; Educação. Abstract This article has a research theme the relationship between the history of an organic intellectual from the state of Pará, Marajó Island, Portel microregion, county of Gurupá, and the struggle in defend access to education. The objective is to describe a life history of the intellectual and talks about more general events that resulted, among other things, in the foundation of the Rural Family House of Gurupá and its proposal of education for the young population of the region. Theoretically, this study was based on history seen from below by Thompson, and Gramsci’s conception of organic intellect. Methodologically, was investigated the Oral History. We used as sources: documents collected in the county of Gurupá, data from a memorial written by Manoel do Carmo and information from semi-structured interviews. After the analysis, it was possible to verify that the life of Manoel do Carmo is indelible articulated to the social struggles that happened into county of Gurupá, linked to the rural workers and education. Keywords: Organic Intellectual, Social Movements, Education.